2007
DOI: 10.1007/s00299-007-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

The rice pathogen-related protein 10 (JIOsPR10) is induced by abiotic and biotic stresses and exhibits ribonuclease activity

Abstract: We previously reported that rice blast fungus or jasmonic acid induced the expression of rice pathogenesis-related class 10 (JIOsPR10) proteins (Kim et al. 2003, 2004). However, no further studies have been carried out to examine the expression, localization, and enzymatic activity of this protein in either developmental tissues or in tissues under abiotic stress conditions. In this study, rice JIOsPR10 was examined by Western blot analysis, immunolocalization, and biochemical assays. Western blots revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 51 publications
1
70
0
2
Order By: Relevance
“…JIOsPR10 was found to possess ribonuclease activity, but did not exhibit direct antifungal activity. The disulfide bonding between cysteine residues of the protein may play a role in constitutive self-defense mechanisms in plants against biotic and abiotic stresses (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…JIOsPR10 was found to possess ribonuclease activity, but did not exhibit direct antifungal activity. The disulfide bonding between cysteine residues of the protein may play a role in constitutive self-defense mechanisms in plants against biotic and abiotic stresses (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…4). Taken together, we strongly suggest that these three PR proteins may play roles in root development under water deficit other than disease resistance response (Kim et al 2001(Kim et al , 2008Hashimoto et al 2004). Concerning the induction mechanisms of PR proteins expression, especially in relation to the crosstalk between various biotic and abiotic stresses, there were only a few reports (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tags for PR-10 ( Kim et al, 2003;McGee et al, 2001;Tanaka et al, 2003) were detected a total of three times, suggesting that the protein seems to make a significant contribution as a biotic stress defense system. Recently, it was reported that the JIOsPR10 protein which is one of the PR-10 family possesses RNase activity that is dependent on sensitive to DTT, suggesting the importance of the disulfide bonding between cysteine residues (Kim et al, 2008a). In addition, expression level using Western blot, immunohistochemical, and its promoter analysis of PBZ1 protein (PR-10 family) is tightly associated with plant cell death tissues, suggesting that PBZ1 could serve as a cell death marker protein as well as defense protein in rice (Kim et al, 2008b).…”
Section: Resultsmentioning
confidence: 99%